Аналіз сучасних архітектур процесорів - Фролова, Н.В.; Гулак, Д.О. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The main trends in modern processor architectures based product developer Intel are analyzed. The technological solutions for improving processor performance according to the strategy Intel in the development of semiconductor technology is considered.